Soil moisture retrieval from bistatic scatterometer measurements using fuzzy logic system - Gupta D.K.; Prasad R.; Srivastava P.K.; Islam T.; Gupta M. (My University, 2025)
Many hydrological processes are strongly dependent on the soil moisture content on top of earth surfaces. In the present study, the fuzzy logic algorithms are used for the retrieval of soil moisture using bistatic scatterometer data. For this purpose, the bistatic scatterometer measurements are performed for the rough soil surface at the incidence angles 20° to 70° steps of 5° for HH-and VV-polarization at di erent soil moisture contents. e linear regression analysis is performed between observed soil moisture contents and bistatic scattering coecients for selecting the suitable incidence angle for soil moisture retrieval. e bistatic scattering coecients at 25° incidence angle are selected as the input data sets for the calibration and validation of fuzzy logic models. e performances of fuzzy models are assessed interms of statistical performance indices %Bias, root mean squared error (RMSE) and Nash-Sutcli e Eciency (NSE). e analysis of the above mentioned indices indicates that the fuzzy model at VV-polarization is found better than HH-polarization. © 2017 by Taylor & Francis Group.